Improving the technical preparation of football players on the basis of the control of discriminative characteristics when performing combinations of techniques during a game - Елена Митова; Вадим Матяш (National University of Physical Education and Sport of Ukraine, 2016)
The paper examines the issue of improving the technical preparation of football players during initial basic training. A special attention is paid to the development and experimental substantiation of the methods of technical preparation of young football players in an annual cycle at the stage of initial basic training on the basis of the control of discriminative characteristics when performing inseparable combinations of techniques during a game. An attempt was made to uncover the underlying causes of a low technical preparedness of football players at different stages of multi-year training and to implement an integrated scientific approach to improvement of the process of technical preparation of 10-11 years old football players in an annual cycle at the stage of initial basic training on the basis of the control of discriminative characteristics when performing inseparable combinations of techniques during competitive activity, along with the peculiarities of psychophysical condition and a level of development of physical qualities. This approach in teaching technical skills will be of interest to specialists and coaches in football, since the pedagogical experiment has determined the effectiveness of the developed methodology.